Facile, High Quality Sequencing of Bacterial Genomes from Small Amounts of DNA - Momchilo Vuyisich; Ayesha Arefin; Karen Davenport; Shihai Feng; Cheryl Gleasner; Kim McMurry; Beverly Parson-Quintana; Jennifer Price; Matthew Scholz; Patrick Chain (International Journal of Genomics)
Sequencing bacterial genomes has traditionally required large amounts of genomic DNA (~1 μg). There have been few studies to determine the effects of the input DNA amount or library preparation method on the quality of sequencing data. Several new commercially available library preparation methods enable shotgun sequencing from as little as 1 ng of input DNA. In this study, we evaluated the NEBNext Ultra library preparation reagents for sequencing bacterial genomes. We have evaluated the utility of NEBNext Ultra for resequencing and de novo assembly of four bacterial genomes and compared its performance with the TruSeq library preparation kit. The NEBNext Ultra reagents enable high quality resequencing and de novo assembly of a variety of bacterial genomes when using 100 ng of input genomic DNA. For the two most challenging genomes (Burkholderia spp.), which have the highest GC content and are the longest, we also show that the quality of both resequencing and de novo assembly is not decreased when only 10 ng of input genomic DNA is used.